PENINGKATAN HASIL BELAJAR TEMATIK MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT PADA SISWA KELAS III SEKOLAH DASAR - Yuanisyah, Risma Febrian; Sumani, Sumani; Markilah, Markilah (JS (JURNAL SEKOLAH), 2023)
Abstract: The purpose of this research is to improve thematic learning outcomes by applying the TGT type of cooperative learning model to students. This study uses the Classroom Action Research (PTK) method which consists of planning, implementing, observing, and reflecting. The research subjects were students of class III Elementary School 1 Karangsoko Trenggalek, totaling 30 students consisting of 13 male students and 17 female students. Research data were analyzed qualitatively and quantitatively. In this study it can be said to be complete if student learning outcomes can meet the specified Minimum Completeness Criteria (KKM), which was 75. Based on the results obtained it can be seen that the application of the TGT type cooperative learning model can improve student learning outcomes. The level of learning completeness in the pre-cycle reaches 33%. Then in cycle I there was an increase of 63%. In cycle II the level of mastery of learning outcomes increased by 87%. Thus it can be concluded that in class III at Elementary School 1 Karangsoko there is an increase in thematic learning outcomes through the application of the TGT type cooperative learning model.Keywords: Cooperative Model, TGT, Learning Outcomes  Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar tematik dengan menerapkan model pembelajaran kooperatif tipe TGT pada siswa. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang terdiri dari perencanaan, pelaksanaan, pengamatan, serta refleksi. Subjek penelitian adalah siswa kelas III SDN 1 Karangsoko Trenggalek yang berjumlah 30 siswa yang terdiri dari 13 siswa laki-laki dan 17 siswa perempuan. Data penelitian dianalisis secara kualitatif dan kuantitatif. Dalam penelitian ini dapat dikatakan tuntas apabila hasil belajar siswa dapat memenuhi Kriteria Ketuntasan Minimal (KM) yang telah ditentukan yakni 75. Berdasarkan hasil yang telah diperoleh terlihat bahwa penerapan model pembelajaran kooperatif tipe TGT dapat meningkatkan hasil belajar siswa. Tingkat ketuntasan belajar pada pra siklus mencapai 33%. Kemudian pada siklus I terjadi peningkatan sebesar 63%. Pada siklus II tingkat ketuntasan hasil belajar meningkat sebesar 87%. Dengan demikian dapat disimpulkan bahwa kelas III di SDN 1 Karangsoko terdapat peningkatan hasil belajar tematik melalui penerapan model pembelajaran kooperatif tipe TGT.Kata kunci : Model Kooperatif, TGT, Hasil Belajar